2021
DOI: 10.1016/j.asmr.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

In-Office Needle Arthroscopy Can Evaluate Meniscus Tear Repair Healing as an Alternative to Magnetic Resonance Imaging

Abstract: Purpose To assess the healing of horizontal cleavage tears of the meniscus 1 year after surgical repair and to determine what modality is best to determine healing. Methods Patients were prospectively followed for 12 months after surgical meniscus repair using a circumferential compression stitch. Inclusion criteria were preoperative magnetic resonance imaging (MRI) evidence of horizontal cleavage tear, age between 18 and 50 years, and no concomitant anterior cruciate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In the clinical situation, IONA has been typically used for younger patients. 4,9 However, IONA would be indicated for any patients, young or old, as long as their medical status allowed it to be performed in the office instead of an operating room. Sixth, only a 1.9-mm arthroscope with 0° was investigated in the present study; regardless, there are other 1.9-mm arthroscopes with a 25° lens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical situation, IONA has been typically used for younger patients. 4,9 However, IONA would be indicated for any patients, young or old, as long as their medical status allowed it to be performed in the office instead of an operating room. Sixth, only a 1.9-mm arthroscope with 0° was investigated in the present study; regardless, there are other 1.9-mm arthroscopes with a 25° lens.…”
Section: Discussionmentioning
confidence: 99%
“…1 Reportedly, IONA can be utilized to diagnose and treat several musculoskeletal disorders, including biceps tenotomy, rotator cuff repair, meniscectomy, meniscal repair, and cheilectomy for hallux rigidus. 4,9,11,15,17,24,29,38 Regarding ankle disorders, Dankert et al 7 reported that IONA was valuable in removing loose osseous bodies that could not be identified by MRI. Colasanti et al 4 reported that IONA for anterior ankle impingement resulted in high patient satisfaction.…”
mentioning
confidence: 99%
“…In-office needle arthroscopy was also used to assess the status of a surgically repaired meniscus. DiBartola et al [ 6 ] demonstrated through in-office needle arthroscopy the healing of four repaired horizontal cleavage tears of the medial meniscus and four of the lateral meniscus six months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Further, in some settings, this procedure has been found to be statistically equivalent in both efficiency and accuracy when compared to diagnostic surgical arthroscopy, and more accurate than MRI, without increased complications. 3 , 4 , 5 Real-time visualization of intra-articular pathology in an office setting can lead to reduced duration of time between diagnosis and ultimate management (whether surgical or nonsurgical), therefore, reducing time between injury and recovery. 6 , 7 Indications for an in-office diagnostic needle arthroscopy of the knee include patients who are unable to obtain an MRI (i.e., due to a pacemaker, claustrophobia, etc.…”
Section: Introductionmentioning
confidence: 99%
“…), patients with suspected intra-articular pathologies, including meniscal tears, chondral lesions, ligament tears, and loose bodies; and further, can be used for second-look arthroscopy following a variety of procedures, including meniscus and/or cartilage repair/restoration when MRI may not provide clear results. 5 , 6 The purpose of this Technical Note is to describe a standard in-office needle arthroscopy technique using the NanoScope™ (Arthrex Inc., Naples, FL) arthroscopy system.…”
Section: Introductionmentioning
confidence: 99%